2019
DOI: 10.1108/jd-10-2018-0172
|View full text |Cite
|
Sign up to set email alerts
|

The reading background of Goodreads book club members: a female fiction canon?

Abstract: Purpose Despite the social, educational and therapeutic benefits of book clubs, little is known about which books participants are likely to have read. In response, the purpose of this paper is to investigate the public bookshelves of those that have joined a group within the Goodreads social network site. Design/methodology/approach Books listed as read by members of 50 large English-language Goodreads groups – with a genre focus or other theme – were compiled by author and title. Findings Recent and yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…It is worth noting that these finding are also reflected in Quantcast 4 Goodreads statistics suggesting that, as of December 2020, in terms of age and gender, an estimated 47% of Goodreads users are between ages 18 and 34, and 58% of users are women. As a social network site, it seems to attract younger users but as a literary site it could also attract older readers (Thelwall and Bourrier, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that these finding are also reflected in Quantcast 4 Goodreads statistics suggesting that, as of December 2020, in terms of age and gender, an estimated 47% of Goodreads users are between ages 18 and 34, and 58% of users are women. As a social network site, it seems to attract younger users but as a literary site it could also attract older readers (Thelwall and Bourrier, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the user-generated reviews are in many ways connected to the scholarly critique as they provide insights into its content. Studies of Goodreads’ user-generated reviews have investigated various aspects of reviews, such as impact of reviewed titles (Kousha et al, 2017; Zuccala et al, 2015), linguistic characteristics of reviews (Hajibayova, 2019), and Goodreads book club members’ reading patterns (Thelwall and Bourrier, 2019). For example, Wang et al’s (2019) analysis of domain differences in attribution of reviews found that highly cited arts and humanities titles tended to receive the most reviews.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies have explored book review collections while several other works have attempted to recreate story plots based on these reviews [26,29,30]. The sentence-level syntax relationship extraction task has been studied widely in work on Natural Language Processing and Open Information Extraction [1,6,7,16,21,31] as well as in relation to the discovery of actant-relationship models for corpora as diverse as conspiracy theories and national security documents [15,20].…”
Section: Related Workmentioning
confidence: 99%
“…These discussions range from explorations of twists and turns in the plot, to simple declarations of admiration for or familiarity with certain actants (characters, places, things). [26] [12] Taken individually, book commentaries and reviews provide a highly individualized perspective on a work of fiction, focusing only on a few actants and their relevance to the narrative. Taken together, these comments provide insight into a broader reader consensus of a novel's overarching narrative framework, comprising a majority of the actants and their nuanced relationships.…”
Section: Introduction 1motivationmentioning
confidence: 99%
“…Estudios precedentes han incidido en que predominan los clubes de lectura donde los lectores son avanzados, pudiendo ser espacios excluyentes para lectores principiantes (Mulas et al 2017;Nolan 2020;Thelwall y Bourrier 2019;Bassett 2017), aunque hay experiencias que combinan ambos perfiles lectores (Álvarez-Álvarez 2016;MacGillivray et al 2019) o dirigidos específicamente a niños, adolescentes, personas sin estudios, estudiantes universitarios, etc. (Cooper 2019;Shaikh et al 2019;Zerden et al 2019;Henderson et al 2020;Ro 2018, ;Dantas et al 2006).…”
Section: Introductionunclassified